Management of epidermal hyperpigmentation with a novel depigmenting formulation: a research survey - Gautam, Manish (International Journal of Research in Medical Sciences, 2023)
Background: Epidermal hyperpigmentation is an important dermatological concern with a high prevalence in the Indian population. Kojic acid-based depigmenting formulations have proven to be effective in the management of epidermal hyperpigmentation. A questionnaire-based survey was conducted to assess physicians’ knowledge about epidermal hyperpigmentation and practice patterns about a novel depigmenting formulation containing a combination of kojic acid dipalmitate 4%, azelaic acid 12%, glycolic acid 3%, niacinamide 4%, arbutin 2%, glycogen liquid 2%, sodium hyaluronate solution 2%, and shea butter 1% for epidermal hyperpigmentation treatment in India. Methods: The survey was conducted among 235 dermatologists across different geographical regions of India over 3 months. The questionnaire evaluated prevalence and choice and duration of therapies for epidermal hyperpigmentation in Indian clinical practice, and dermatologists’ real-life experience with efficacy of the novel formulation. Descriptive statistics were used to summarize survey results. Results: All 235 dermatologists completed the questionnaire and responded to questions based on experience in treating patients with epidermal hyperpigmentation. In all, 58% dermatologists preferred kojic acid-based combinations. Furthermore, 57% of dermatologists agreed that glycolic acid can enhance the penetration of kojic acid and azelaic acid, 47.45% strongly agreed that a kojic acid-based formulation could be a safe alternative to steroid and hydroquinone-based formulations. Overall, 67% of dermatologists agreed that the kojic acid-based formulations with additional moisturizers helped in faster resolution of epidermal hyperpigmentation compared to other depigmenting formulations. Conclusions: The survey findings indicate that the novel kojic acid-based formulation with additional moisturizers could be a preferred choice for epidermal hyperpigmentation management.